Transient leucopenia in acute zinc phosphide poisoning - Keyal, Niraj; Paneru, Hem Raj; Shrestha, Gentle Sundar; Amatya, Roshana (Journal of Chitwan Medical College, 2017)
Zinc phosphide is easily available, cheap, and highly effective household rodenticide. Self poisoning with this rodenticide is commonly encountered in our clinical practice and causes lethal poisoning by liberation of phosphine which in turn causes inhibition of cytochrome oxidase C thereby leading to cellular hypoxia. We report a case of such poisoning which had an unusual presentation in the form of transient leucopenia.